Characterization of the complete mitogenome of Gymnocypris dobula (Günther, 1868) (Cypriniformes: Cyprinidae). Issue 1 (2nd January 2022) - Li, Jiasheng; Chen, Shiyi; Lahm, Tashi; Peng, Ying; Shen, Haodi; Zhang, Kun; Huang, Wenhua; Liang, Xudong; Liu, Bingjian; Chen, Meiqun
Abstract: Gymnocypris dobula, classified into the highly specialized Schizothoracine fish, is endemic to Tibet, China. The complete mitochondrial DNA sequence of G. dobula was 16, 728 base pairs in length and comprised 22 transfer RNA genes, 13 protein-coding genes, two ribosomal RNA genes as well as one control region as in a typical vertebrate mitochondrial DNA gene. The ML and BI trees showed that G. dobula was most closely related to Gymnocypris scleracanthus within the highly specialized group. This mitogenome provides new molecular data for further taxonomic and phylogenetic studies of Schizothoracine fish.